Domestic resource mobilization by social movement organizations in Latin America : a case study of the Abrinq Foundation for children rights of Brazil - Coronado, Carlos (2008)
The aim of this Master’s thesis is to study the feasibility and sustainability of mobilizing domestic resources to advance social movement causes in Latin America. The question is based on the understanding that Social Movement Organizations (SMO) can mobilize the resources –funds and labor- of domestic elite instances in order to favor their beneficiary bases. The thesis proposes a Domestic Resource Mobilization (DRM) approach and addresses various theoretical and practical concerns regarding the qualitative impact of that conception in the work of Social Movement Organizations. The specific focus of is centered on resource mobilization strategies and initiatives conducted by the SMO Abrinq Foundation for Children Rights of Brazil. The theoretical framework of this thesis is constructed upon the academic debate among different authors in the field of social movements; within this field of knowledge, the specific research areas of resource mobilization and public policy outcomes of social movements are of particular interest. This seeks to provide a pertinent conceptual structure for the analysis of the resource mobilization strategy implemented by the case study. Complementarily, literature focused on the foreign aid regime and its impact in the resource mobilization initiatives carried on by SMOs in Latin America is utilized to provide a historical context to the concept of DRM. The case study material of this research consists of documents produced by the Abrinq Foundation in which it describes and evaluates its programs, projects and institutional vision; policy documents published by the federal Executive of Brazil, accounting for compromises made within the framework of Abrinq Foundation’s programs; and interviews conceded by representative members of the Abrinq Foundation to different Brazilian media outlets. The analysis of Abrinq Foundation’s programs provides a moderately positive perspective regarding the feasibility and sustainability of a DRM approach by SMOs in Latin America.